Mranʻ māʹ nanʻʺ suṃʺ chaṅʻ : Mranʻ mā mhu ʼa chaṅʻ ʼa lā nhaṅʻʹ chaṅʻ ratanā (Cinʻ Panʻʺ Mruiṅʻ Cā pe tuikʻ, 1980)
On elephants and their uses as transport by Burmese royalty as described in classical literature.